Difficulties in Translating Conjunctions in Arabic and English Languages: Study Based On Translation Students of South Eastern University Of Sri Lanka - NM Mohamed Rizvi; MHA Munas; Iqbal Saujan (Departement of Arabic Language and Literature, IAIN Syekh Nurjati Cirebon, 2021)
Each language has its own set of rules. Based on this, the rule of conjunctions in the Arabic language differs from the English language, because they come from two separate language families. Thus, the learners of Arabic and English languages as a foreign language face difficulty and commit mistakes in identifying meanings of conjunctions. Therefore, this Study focuses on identifying difficulties when translating. This study employed a descriptive and contrastive methodology. The data were gathered from interviews and questionnaire that were distributed to all specialization Students in linguistic and translation from South Eastern University of Sri Lanka. MS Excel Software was used for the data analysis. The findings show, the students face difficulties in determining appropriate conjunctions and understanding their meaning, using suitable words. Based on the researcher's findings, continuous training in translation with caring of grammatical errors is recommended. This research will help foreign language learners, translators and studentsكل لغة لها مجموعة القواعد الخاصة بها. وبناءً على ذلك ، فإن قاعدة الاقتران في اللغة العربية تختلف عن اللغة الإنجليزية ، لأنها تأتي من عائلتين لغويتين منفصلتين. وبالتالي ، يواجه متعلمي اللغتين العربية والإنجليزية كلغة أجنبية صعوبة ويرتكبون أخطاء في تحديد معاني الاقتران. لذلك ، تركز هذه الدراسة على تحديد الصعوبات عند الترجمة. استخدمت هذه الدراسة منهجًا وصفيًا ومقابلًا. تم جمع البيانات من المقابلات والاستبيانات التي تم توزيعها على جميع طلاب التخصص في اللغويات والترجمة من جامعة جنوب شرق سريلانكا. تم استخدام برنامج MS Excel لتحليل البيانات. تظهر النتائج أن الطلاب يواجهون صعوبات في تحديد الاقترانات المناسبة وفهم معانيها باستخدام الكلمات المناسبة. بناءً على نتائج الباحث ، يوصى بالتدريب المستمر في الترجمة مع مراعاة الأخطاء النحوية. سيساعد هذا البحث متعلمي اللغات الأجنبية والمترجمين والطلاب.